Menggali dampak lompat tinggi, fleksibilitas, dan kepercayaan diri terhadap akurasi smash atlet sepak takraw - Ayu, Putri; Alnedral, Alnedral; Yanuar Kiram , Phil; Padli, Padli; Zarya, Fiky (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
The inaccuracy of the Smash of sepak takraw athlete is influenced by several factors, such as jump height, flexibility, and confidence. The purpose of this research is to uncover and prove the direct, indirect, and simultaneous influence of jump height, flex, and confidence on the smash accuracy of sepak takraw athletes. This research type is quantitative and associative with an approach through path analysis (Path Analysis). A total of 20 samples of Muaro Bungo PSTI sepak takraw athletes were PSTI (persatuan sepak takraw seluruh indonesia) age (20 tahun) gender (10 woman, 10 man). Instrument height jumps using Vertical Jump, flexibility using Flexiometer, confidence using questionnaires, and accuracy tests Smash sepak takraw. The data were analyzed using path analysis with structural model testing at α = 0.05. The results findings indicate that jump height (26.52%), flexibility (5.06%), and confidence (25.5%) have direct positive effects on sepak takraw smash accuracy. Moreover, jump height indirectly influences accuracy through confidence (40.44%), while flexibility indirectly impacts accuracy through confidence (1.06%). Simultaneously, jump height, flexibility, and confidence collectively explain 89.7% of the variance in smash accuracy. In summary, the study reveals that higher jump height, greater flexibility, and increased confidence significantly contribute to improved sepak takraw smash accuracy, aligning with the research objectives. Based on the results above, the conclusion is that there is a high influence of jumping, flexibility, and confidence on the accuracy of the smash of PSTI Muaro Bungo sepak takraw athletes.